Strategies to cope with psychological combustion among school leaders in Riyadh - Alhazzani, Eman Turkey (Journal of Educational and Psychological Sciences, 2022)
This study aimed to find out the degree of psychological combustion of school leaders in Riyadh, to identify effective coping strategies among school leaders from their point of view, as well as to identify demographic and administrative characteristics that are more capable of distinguishing between degrees of psychological combustion. To achieve the goal of the study, the descriptive survey method was used through the design of a two-axis questionnaire, the first based on the Maslach functional combustion scale, and the second for five response strategies designed by the researcher. The study community of (1525) is the leader of a public and community school, and the questionnaire was distributed to a sample of (324) school leaders. The results of the study concluded that the degree of psychological combustion among school leaders in Riyadh was large and averaged (89.76), and it was found that the most prominent degree of psychological combustion was after psychological stress on average (36.86), followed by a sense of personal achievement with an average (33.52), and finally came after an average of (19.38) feelings. The results revealed that the most prominent strategies for countering effective psychological combustion among the leaders of Riyadh schools were a strategy (commitment to the social role), followed by a strategy (problem solving), followed by a strategy (social support), followed by a strategy (emotion), and finally a strategy (avoidance). The study also revealed that there are no statistically significant differences between the opinions of the study sample on the degree of psychological combustion of the variables of the academic qualification and years of experience, but there are statistically significant differences at the level (0.01) and less between the vocabulary of the study sample their primary school stage and the vocabulary of the study sample their middle stage of study about (sag feelings) in favor of the middle stage. There are statistically significant differences at (0.05) and lower between the vocabulary of the study sample, their middle school stage and the vocabulary of the study sample, their secondary school stage on (sag feelings) for the secondary level. The study recommended urging female leaders to participate in proposing and providing solutions, the participation of parents as well, and the distribution of work to educational staff.